If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -17) = (5x + 8) Reorder the terms: (-17 + 2x) = (5x + 8) Remove parenthesis around (-17 + 2x) -17 + 2x = (5x + 8) Reorder the terms: -17 + 2x = (8 + 5x) Remove parenthesis around (8 + 5x) -17 + 2x = 8 + 5x Solving -17 + 2x = 8 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -17 + 2x + -5x = 8 + 5x + -5x Combine like terms: 2x + -5x = -3x -17 + -3x = 8 + 5x + -5x Combine like terms: 5x + -5x = 0 -17 + -3x = 8 + 0 -17 + -3x = 8 Add '17' to each side of the equation. -17 + 17 + -3x = 8 + 17 Combine like terms: -17 + 17 = 0 0 + -3x = 8 + 17 -3x = 8 + 17 Combine like terms: 8 + 17 = 25 -3x = 25 Divide each side by '-3'. x = -8.333333333 Simplifying x = -8.333333333
| 10+9i= | | 4=-1(n+11) | | 0.5x^2+2.2x=-3.6 | | o=-4a-7a | | 2(p+2)=1.8p-2-0.2(p+2) | | 5h-3h+6= | | 3(3y-9)=-2(y-3) | | -9=-5+4(-y+4)-5(4+3y) | | 3(3y-9)=-2(-3) | | 7x+1=5x+35 | | -7+x*5=-20 | | (3x+29)=(4x-9) | | 6.63x+81=43.9569+9x | | 4x-2(-2x)=6 | | -12=-x-x | | 12x+30=6x-12 | | -54=9d | | 7=x*17+3 | | 15x-3=102 | | 2x-y+3z=37 | | (2k+1)(4k-1)=0 | | 3-4(5-(-7))+3(2)= | | -18=6(2+k) | | 3x+48=6x+3 | | -8=-3+x*-6 | | 30-2a=5 | | 20y=14 | | 2x+1y=7.50 | | 15+q(6)=-21 | | 4x^2+36-4=0 | | (8x+3)(3x^2+6x+6)= | | -5+x*-3=6 |